Analysis of the theme of scientific dissemination in the Common National Curriculum Base and survey of websites for use in Basic Education (Research, Society and Development, 2022)
Knowing a variety of types of scientific texts, from media reports to scientists' originals, is a condition for becoming a participant in scientific culture. In this context, this research aims to analyze how scientific dissemination (SD) is present in the Common National Curriculum Base (CNCB), and to indicate SD sites to be used in teaching science on Basic Education (BE). Qualitative and exploratory in nature, the first stage corresponded to a documental analysis on the SD approach in the area of Natural Sciences (NS). Therefore, we performed a random, non-probabilistic and convenience search on the Google search platform, in order to find scientific dissemination websites to be used in teaching science on BE. Seven websites for children and young people in primary and secondary education were selected: BBC – Ciência; Ciência Hoje; Galileu; Revista Fapesp; Scientific American Brasil; Space Today; and Superinteressante. The criteria adopted in the selection of sites were to present scientific evidence; proper language; reliability of data; and contextualization of themes. Out of a total of 61 mentions, the term set 'scientific dissemination' was mentioned in the NS area of high school, in only one specific competency that addresses a single skill. We understand that it is necessary to expand the scope of SD, since the appropriation, by the students, of knowledge in the area of NS has become essential. Finally, it is necessary to present people with reliable sources and also that teaching and research institutions work more and more in SD.